Metafrontier analysis of technology gap and productivity difference in African agriculture - Nkamleu, G.B.; Nyemeck, J.; Sanogo, D. (2006)
Agricultural productivity in Africa from 1971 to 2000 is examined using the recently developed metafrontier function technique, for the purpose of studying differences in efficiency and technology gap across different regions of the continent. The results support the view that technology gap plays an important part in explaining the ability of agricultural sectors in one region to compete with agricultural sectors in different regions in Africa. The study has also evidenced that average technical efficiency score of the agricultural sector has been almost stable over time, while a marginal decrease of the productivity potential over the 30 years period was observed.